Методологическое введение к курсу "Отечественная история": хрестоматия - практикум - Гузарова Н. И. Надежда Ивановна; Гузаров В. Н. Владимир Николаевич; Трубникова Н. В. Наталья Валерьевна (Томск, Изд-во ТПУ, 2012)
Заглавие с титульного экрана